Merefleksikan Kembali Konsep Keselamatan dalam Perspektif Teologi Kontemporer dan Kaitannya dengan Praksis Pastoral - Natalia; Bani, Endang Puspita (STT Pelita Dunia, 2025)
This article aims to reflect on the concept of salvation in the light of contemporary theology and relate it to the pastoral practice of the church today. The concept of salvation, which has often been understood in an individualistic and eschatological manner, has now been revised to be more inclusive, contextual, and transformative. Using a literature study method and a descriptive-analytical approach, this article reviews the development of the understanding of salvation from time to time, as well as its impact on pastoral thought patterns and actions. It is emphasized that salvation is not only a spiritual gift from God, but also a process that changes personal and social life. Therefore, the church needs to develop a pastoral practice that is adaptive, empathetic, and relevant in facing the challenges of the times. The emphasis on the aspects of forgiveness, repentance, justification, and peace is the foundation of service that touches all dimensions of the congregation's life.